Implementasi Metode Single Moving Average pada Aplikasi Order Indent Berbasis Web - Johny Soetikno; Sitti Aisa; Reza Selviana; Gusti Fernando (Universitas Muhammadiyah Riau, 2022)
PT. Hadji Kalla is Toyota's official distributor for South Sulawesi, Central Sulawesi, West Sulawesi and Southeast Sulawesi. In running its business, the sales department often has difficulty meeting the public's need for Toyota brand car products, especially in handling the demand for cars that are indented. Indent orders occur due to increased orders but less car stock. To handle indent orders, it can be done by forecasting future consumer needs using previous data, it is necessary to design a sales forecast application using the single moving average method. The purpose of this study is to implement the single moving average method to reduce the demand or order for indent cars, and to test the system using the white-box method. The prediction results of indent car sales in August 2022 are 654 units with a MAPE value of 17.19%, and normal car predictions in August 2022 are 2.842 units with a MAPE value of 22.9%. The results of testing the system using the black-box method on the 18 modules, it was found that all the forms that were designed as a whole had worked as expected.